National policy and mechanisms of development of local infrastructures for leisure-time physical activity - the Impala project - Michal Kudláček; Jana Vašíčková; Filip Neuls (Palacký University Olomouc, 2012)
BACKGROUND: Inter-sectoral collaboration and social equity for all inhabitants of European Union in the sphere of approaching infrastructure for leisure-time physical activity (PA) were the main reasons for implementation and financing of international project IMPALA. The project was divided into three stages. AIM: The aim of presented part of IMPALA project is to assess national policy (legislation and regulation) of the development of local infrastructures for leisure-time PA. METHODS: According to the requirements established by project coordinator we carried out structured qualitative interviews with experts and policy makers on diﬀerent decision-making levels. Further, the invited representatives of end users participated in focus group meeting. Also various available sources and documents were used for detailed analysis. RESULTS: Qualitative interviews provided information, which includes the issue of sports facilities in terms of national level and which documents deal with them. At the regional level whole sphere of infrastructures for leisure-time PA is organized by local and regional governments (municipalities). Participants in the focus group meeting shared with others their own positive and negative experiences with the management of infrastructures and finally made some concrete recommendations. The issue of mechanisms for infrastructure development devotes firstly to the relevant conceptual documents at national and regional level, and then describes specific examples of Olomouc and the Olomouc region in terms of planning, financing, construction and management of infrastructures for leisure-time PA. CONCLUSION: In this part of the project we found out that in the Czech Republic there is no specific national political strategy for the development of infrastructures for leisure-time PA. Development is done primarily at the local level. The biggest problem faced by end-operators is the lack of financial resources and outstanding legislation. On the other hand, participation of representatives of various stakeholder groups is appreciated in planning processes for the development of local infrastructures for leisure-time PA.